ADAM33 Silencing Inhibits Vascular Smooth Muscle Cell Migration and Regulates Cytokine Secretion in Airway Vascular Remodeling via the PI3K/AKT/mTOR Pathway. (31st August 2022) - Yan, Fang; Hu, Xin; He, Long; Jiao, Kegang; Hao, Yanyan; Wang, Jing
Abstract : Introduction . Vascular smooth muscle cells (VSMCs) are highly involved in airway vascular remodeling in asthma. Objectives . This study aimed to investigate the mechanisms underlying the effects of a disintegrin and metalloproteinase-33 (ADAM33) gene on the migration capacity and inflammatory cytokine secretion of VSMCs. Methods . Human aortic smooth muscle cells (HASMCs) were transfected with lentiviral vectors carrying short hairpin RNA (shRNA) targeting ADAM33 or negative control vectors. The migration capacity of HASMCs was evaluated by a transwell assay. The levels of secreted inflammatory cytokines were measured using enzyme-linked immunosorbent assay (ELISA) kits. Reverse transcription-quantitative polymerase chain reaction and Western blot assays were performed to detect mRNA and protein expression levels. Results . Silencing of ADAM33 significantly inhibited the migration of HASMCs. The expression of tumor necrosis factor alpha (TNF- α ) in the supernatant of HASMCs was decreased, while that of interferon gamma (IFN- γ ) was increased after the transfection of shRNA targeting ADAM33. Insufficient ADAM33 expression also suppressed the expression levels of phosphatidylinositol 3-kinase (PI3K), phospho-protein kinase B (AKT), phospho-mammalian target of rapamycin (mTOR), Rho-associated protein kinases, phospho-forkhead box protein O1 (FOXO1), and cyclin D1, but it did not affect the levels of AKT, mTOR, or Rho. Conclusion. Silencing of the ADAM33 gene inhibited HASMC migration and regulated inflammatory cytokine secretion via targeting the PI3K/AKT/mTOR pathway and its downstream signaling. These data contribute to a better understanding of the regulatory mechanisms of airway vascular remodeling in asthma.